First evidence of active transpressive surface faulting at the front of the eastern Southern Alps, northeastern Italy: Insight on the 1511 earthquake seismotectonics - Falcucci, Emanuela; Eliana Poli, Maria; Galadini, Fabrizio; Scardia, Giancarlo [UNESP]; Paiero, Giovanni; Zanferrari, Adriano (Copernicus Publications, 2018)
We investigated the eastern corner of northeastern Italy, where a system of NW-SE-trending dextral strike-slip faults of western Slovenia intersects the south-verging fold and thrust belt of the eastern Southern Alps. The area suffered the largest earthquakes of the region, among which are the 1511 (Mw 6.3) event and the two major shocks of the 1976 seismic sequence, with Mw= 6.4 and 6.1. The Colle Villano thrust and the Borgo Faris-Cividale strike-slip fault have been here first analyzed by interpreting industrial seismic lines and then by performing morphotectonic and paleoseismological analyses. These different datasets indicate that the two structures define an active, coherent transpressive fault system that was activated twice in the past two millennia, with the last event occurring around the 15th-17th century. The chronological information and the location of the investigated fault system suggest its activation during the 1511 earthquake.